Adherence to Attendance at Outpatient Clinic and Longterm Survival of Patients after Stroke in Outpatient Setting: the Data of REGION-M Registry - S. Yu. Martsevich; S. N. Tolpygina; M. I. Chernysheva; A. V. Zagrebelny; V. P. Voronina; M. M. Lukyanov; N. P. Kutishenko; N. A. Dmitrieva; O. V. Lerman; Yu. V. Lukina; S. V. Blagodatskikh; E. Yu. Okshina; et al. (Рациональная фармакотерапия в кардиологии, 2021)
Aim. Assess the two-year survival rate of patients who have undergone acute cerebral circulation disorder, depending on their commitment to visiting the district polyclinic before and after discharge from the hospital.Material and methods. The outpatient part of the REGION-M register included 684 patients attached to the Moscow City Polyclinic №64, discharged from the Moscow City Clinical Hospital n.a. F.I. Inozemtsev of from 01.01.2012 to 04.30.2017 with a confirmed diagnosis of acute cerebral circulation disorder (cerebral stroke / transient ischemic attack).Results. Of the entire cohort, 83.2% of patients and 84.2% after hospital discharge attended the clinic during the year before the development of reference acute cerebral circulation disorder. Patients who attended the clinic before and after the reference stroke were older, more likely to have diabetes, comorbid disease and disability. For 22 months of follow-up, mortality was 28.8% (197 out of 684 people). Among those who applied and did not apply to the clinic before the reference acute cerebral circulation disorder, the difference in mortality tended to be reliable (27.4% versus 35.7%, p <0.1), while mortality was almost twice as low among patients who applied to the clinic at least 1 time after discharge (25.7%) than among patients who did not apply after discharge - 45.4%, p<0.0001. When adjusting for sex and age (the relative risk of death for them was 1.009, 95% confidence interval 1.005-1.01 2, p<0.0001 ), the statistical validity of reducing the risk of death was maintained when patients were committed to visiting the clinic after discharge - the relative risk of death 0.366 (95% confidence interval 0.269-0.500, p<0.0001 ).Conclusion. Lower mortality among those who visited the district polyclinic after undergoing stroke confirms the important role of medical observation in the posthospital period. At the same time, there is a reserve in improving the long-term prognosis of the lives of patients who have suffered a cerebral stroke or transient ischemic attack, due to greater coverage of patients with medical supervision in the clinic.